Explanation and Analysis of the Inequalities of Health Development Services Using Multi-Criteria Decision-Making Methods (Case study: Golestan Province) - Khodarahm Bazi; ebrahim moammare (جغرافیا و توسعه, 2017)
The study of health indices and their distribution patterns in different geographic spaces causes the imbalance in health facilities distribution to be better identified and planning for their fair distribution and access of all people to the desired services to be realized as desirable. The present study uses descriptive-analytical method and by using 11 health indicators has analyzed and explained the inequality in health care services and its distribution in the county of Golestan province. In this regard, TOPSIS, SAW and Pearson's coefficient of skewers were used for ranking and Enhanced Shannon used for scoring. For analyzing data, EXCEL statistical software was used and for non-quantifying data, the non-linear and linear methods were used. Also, ARC GIS 9.3 software was used for the space displaying. Data and information was collected by documentary and library method. The findings of the research indicate that distribution of health indicators in Golestan province is polarized and uneven, so that the city of Gorgan is the most favored city of the city and  Maravetappe city is the most deprived city in the province. The results of the study reveal the necessity of a justice-centered view in the field of planning and efforts to create the optimal spatial deployment of these services and indicators in the province of Golestan.